PERANCANGAN PROTOTYPE SOUVENIR KUSTOM YANG MENJADI PRODUK AWAL DARI FRY WORKSHOP - Fernando Adiga Wijaya; Rendy Iswanto (Jurnal Vicidi, 2016)
“FRY Workshop” is a studio that make and producing clay toys called “Figure”. In Surabaya nowadays, it’s very rare to find business that offers service for making a souvenir in the shape of “Figurines”. It’s why the purpose of this research is to know what are our target market wants for this product. With quantitative research method, the results are many of the consumer are interested and accepted for this customized “Figure” service in accordance with their wishes, a unique packaging is required for making this product into a souvenir or gifts. This is a business chance for FRY workshop.